Impact of Service Quality on Customer Satisfaction of Ekta Books with View of School Clients of Kathmandu Valley - Tamang, Tulsi (Sotang, Yearly Peer Reviewed Journal, 2022)
This topic of study aims at finding out whether the customers’ expectations of matched their satisfaction level on the basis of quality and after sales services provided by Ekta Books. So, the research is to study the preference of the customers and their satisfaction level. A structured questionnaire designed and survey was conducted among 100 retailers/dealers, organizational staff/customers and individual customers through probabilistic systematic sampling technique. With a view to remaining competitive leading position and for businesses to grow, service quality and customer satisfaction are key ingredients. These two paradigms are rather different concepts; however, they are closely correlated. (Sureshchandar, 2003). The purpose of this study was to describe how customers perceive service quality and whether they are satisfied with services offered by Ekta Books. The thrust of this study was to compose an assessment of service quality and customer satisfaction in Ekta Books one of the pioneers in book publishing and distribution in Nepal. It is one among the line of a few book publishers that have successfully completed a long journey. Its quality in both material and content in textbooks and academic books is unrivalled. The questionnaire was developed and distributed using a convenience sampling technique among 100 respondents in the Kathmandu Valley. From the analysis, it was found that the overall service quality in Ekta Books was relatively high and that the customers were satisfied with the services of Ekta Books. Further, the analysis proved that the dependency of customer satisfaction on the quality of services and that this relationship was a very high positive correlation. The respondents were found satisfied with the speed of delivery, reliability, quality and value-for-money for the products and services. It appears that the company is very much concerned with the satisfaction of clients as it promptly responded to the issues of customer complaints and dissatisfaction. The researcher makes a few recommendations based on the findings of the study. First of all, the management of Ekta Books should pay attention to improve the service quality and other factors which may lead to customer satisfaction thereby improving its performance and the overall brand image and profitability of the Company.